2010
DOI: 10.15376/biores.6.1.373-385
|View full text |Cite
|
Sign up to set email alerts
|

Densification of wood veneers combined with oil-heat treatment. Part 1: Dimensional stability

Abstract: is often a problem due to compression recovery. Alternatively, oil-heat treatment (OHT) improves wood dimensional stability and enhances resistance to biological attack. This study examined combined wood densification and OHT. Large wood veneer 700 700 mm specimens prepared with aspen (Populus tremuloides) were densified using heat, steam, and pressure at 160ºC, 180ºC, and 200°C, respectively. OHT at 180, 200ºC, and 220ºC for 1, 2, and 3h was then applied to the densified veneers. Results show that OHT efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…To combine favourable effects, some researchers have analysed the behaviour of wood subjected to densification and subsequently to OHT. Fang et al (2011) observed that in wood treated in this way the equilibrium moisture and the springback were reduced, and this reduction was greater in the samples treated with OHT at higher temperatures. Hsu et al (1988) and Laborie (2006) indicated that in this combined treatment there was a joint occurrence of a reversible swelling due to the hygroscopicity of the wood and another irreversible swelling due to the compression-set recovery.…”
Section: Obtained Increases In Moe Andmentioning
confidence: 86%
See 1 more Smart Citation
“…To combine favourable effects, some researchers have analysed the behaviour of wood subjected to densification and subsequently to OHT. Fang et al (2011) observed that in wood treated in this way the equilibrium moisture and the springback were reduced, and this reduction was greater in the samples treated with OHT at higher temperatures. Hsu et al (1988) and Laborie (2006) indicated that in this combined treatment there was a joint occurrence of a reversible swelling due to the hygroscopicity of the wood and another irreversible swelling due to the compression-set recovery.…”
Section: Obtained Increases In Moe Andmentioning
confidence: 86%
“…Hsu et al (1988) and Laborie (2006) indicated that in this combined treatment there was a joint occurrence of a reversible swelling due to the hygroscopicity of the wood and another irreversible swelling due to the compression-set recovery. Fang et al (2011) quantified the incidence of the irreversible swelling by performing saturation tests on the samples, and observed that it decreased as the time and the treatment temperature increased.…”
Section: Obtained Increases In Moe Andmentioning
confidence: 99%
“…The radial hardness values gradually decreased as the thermal treatment duration increased. However, the hardness value gradually decreased as the thermal treatment temperature and duration increased (Perçin 2012;Fang et al 2012b;Agnieszka 2017). The temperature and duration of the thermal treatment accounted for 30% of the wood hardness variability, whereas the interaction between temperature and duration accounted for 23% of the wood hardness variability (Agnieszka 2017).…”
Section: Radial Hardness Analysismentioning
confidence: 99%
“…However, in the densification processes, there is an increase in surface hardness [41][42][43][44][45]. In addition, it has been reported that both the modulus of elasticity and the modulus of rupture increase with the density [46][47][48][49]. Although these processes can improve certain properties in wood, they do not focus on increasing the stiffness.…”
Section: Introductionmentioning
confidence: 99%